2011
DOI: 10.1002/smll.201101422
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Human Endothelial Cells with Gold Nanoparticles of Different Morphologies

Abstract: The interactions between noncancerous, primary endothelial cells and gold nanoparticles with different morphologies but the same ligand capping are investigated. The endothelial cells are incubated with gold nanospheres, nanorods, hollow gold spheres, and core/shell silica/gold nanocrystals, which are coated with monocarboxy (1-mercaptoundec-11-yl) hexaethylene glycol (OEG). Cell viability studies show that all types of gold particles are noncytotoxic. The number of particles taken up by the cells is estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 53 publications
8
104
0
1
Order By: Relevance
“…A number of studies with AuNPs have shown that size, shape, concentration, and surface modification of the NPs affect the interaction with cells and may lead to varying degrees of internalization and cytotoxicity. [3][4][5][6] Modifying the surface of AuNPs with polyethylene glycol (PEG) has been demonstrated to prolong the circulation time in vivo, 7,8 this being explained by a reduced renal filtration 9 In addition, it has been demonstrated that 15 nm PEGylated AuNPs do not affect platelet aggregation, nor do they induce pro-inflammatory cytokines in endothelial cells. 10 In previous studies it was also shown that PEGylated AuNPs of different sizes did not reduce cell viability or induce cellular stress and were internalized in low amounts by various microvascular endothelial cells compared to the same AuNPs functionalized with various surface polymers.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies with AuNPs have shown that size, shape, concentration, and surface modification of the NPs affect the interaction with cells and may lead to varying degrees of internalization and cytotoxicity. [3][4][5][6] Modifying the surface of AuNPs with polyethylene glycol (PEG) has been demonstrated to prolong the circulation time in vivo, 7,8 this being explained by a reduced renal filtration 9 In addition, it has been demonstrated that 15 nm PEGylated AuNPs do not affect platelet aggregation, nor do they induce pro-inflammatory cytokines in endothelial cells. 10 In previous studies it was also shown that PEGylated AuNPs of different sizes did not reduce cell viability or induce cellular stress and were internalized in low amounts by various microvascular endothelial cells compared to the same AuNPs functionalized with various surface polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with TEM showed the capability of measuring individual hollow gold NP as small as 50 nm with a short integration time per image of 0.2 s. The system also allows identification of these individual hollow gold NP in fixed cell preparations, at illumination intensities < 0.5 W/cm 2 . Such intensities have been shown to result in minimal toxicity for cells incubated with metal NPs 18 . This advantage of using a scanned illumination source will be important for future live cell studies of nanoparticle uptake and processing in cells, where phototoxicity is currently a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the application of a broad spectrum of irradiation at once can produce a significant heating of the particle, which is especially unfavorable for in-vitro studies of sensitive biological systems. 17,18 Further, applications involving NP counting and/or tracking favor a wide-field approach in combination with spectroscopic characterization. Various different approaches have been presented based on hyperspectral imaging where individual spectral components are filtered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GALA's transition from random coil to an amphiphilic α-helix roughly occurs when the pH is decreased from 7 to 5, the pH of inflection between the two conformational states was reported to be near pH 6. [9][10][11][12] At low pHs the Glu sites are protonated and uncharged. The hydrophobic periodicity of the EALA repeats allows the peptide to fold into a stable amphiphilic helix with hydrophobic leucine and alanine sites on one, and hydrophilic glutamic acids on the other side of the helix (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%